Promotion on Social Networks of Artistic Spaces of Carabanchel (Madrid) - Treviño Avellanada, Carlos (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
The artists' studios and exhibition spaces opened in the last decade in Carabanchel are a clear example of the displacement towards the peripheries of several cities as a result of the processes of speculation and gentrification. The success of these dynamics depends on the digital communication technologies, especially those of promotion through social networks. The present research studies the context and the process of conformation of the artistic space of Carabanchel and an analysis of the communicative actions carried out through the social networks Instagram an X, and their link with other media.